Painting the CANVAS - Dhungana, V; Sthapit, B; Sigdel, B (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i3.2749 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 334-335